Identification of the Patterns Produced in the Offensive Sequences That End in a Goal in European Futsal - Amatria, Mario; Álvarez, Javier; Ramírez, Javier; Murillo, Víctor (Frontiers in Psychology, 2021)
Victory is the ultimate goal to be achieved in high performance sports, when it comes to team sports the goal is the key that allows us to achieve that victory. This is the case of futsal, which due to its internal structure as well as its speed in the development of its game makes the achievement of a goal not an isolated event, but rather a higher score is necessary to achieve said victory. The aim of the present study is to analyze the construction of the offensive sequences that have resulted in the score of goals by the two main European futsal leagues, the Spanish and the Italian ones, as well as identifying the patterns corresponding to their offensive actions and which have ended up with the scoring of a goal. The observational methodology has been used for the development of the research and an ad hoc observation instrument has been developed for this purpose. The analysis of the data has been carried out using inferential statistics as well as the sequential analysis of delays as a diachronic analysis in order to identify the patterns of the offensive actions. The results obtained allow the recognition of own conduct patterns in the achievement of the goals scored in each one of the leagues studied. The results obtained will allow experts to have a better understanding of how the goals are scored and how to establish more specific training tasks, both in attack and defense.